DESIGNING ADMINISTRATIVE JUSTICE - Sossin, Lorne (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
This article explores the adaptation of design thinking to administrative justice. The human centred design perspective has been missing from most debates surrounding the design and reform of administrative tribunals in Canada. As a result, the author asserts that the administrative justice system in Canada at all levels of government (federal, provincial, municipal, and Indigenous) is generally fragmented, poorly coordinated, and under-resourced in relation to the needs of its users and has multiple barriers of entry. This article is divided into two parts. The first part reviews the development of design thinking in the context of legal services and legal organizations. The second part explores the implications of this development for administrative justice, particularly in the context of the establishment of new tribunals. Several examples of tribunal reform are examined from a design thinking perspective. By way of conclusion, the author suggests the criteria that should be applied to evaluate the design of a new administrative tribunal.